Optical upconversion devices based on photosensitizer-doped organic light-emitting diodes - Lu, Jiashu; Zheng, Yuan; Chen, Zhijian; Xiao, Lixin; Qihuang Gong (APPLIED PHYSICS LETTERS, 2007)
The optical upconversion of infrared light to visible light has been achieved in photosensitizer-doped organic light-emitting diodes, where poly(N-vinylcarbazole) doped with infrared photosensitizer of 2,4,7-trinitro-9-fluorenylidene malonitrile was used as hole-transporting layer, and tris(8-hydroxyquinoline) aluminum acted as both emitting and electron-transporting layers. Both electroluminescent intensity and current were enhanced under infrared illumination. The enhancement ratio was obtained as 2.45 times for electroluminescent emission and 1.45 times for current. This work brought forth a prototype design for novel flexible organic optical upconversion device used in near infrared field. (c) 2007 American Institute of Physics.